Sustainable low-field cardiovascular magnetic resonance in changing healthcare systems. (14th February 2022) - Qin, Cathy; Murali, Sanjana; Lee, Elsa; Supramaniam, Vaishnavi; Hausenloy, Derek J; Obungoloch, Johnes; Brecher, Joanna; Lin, Rongyu; Ding, Hao; Akudjedu, Theophilus N; Anazodo, Udunna C; Jagannathan, Naranamangalam R; et al.
Abstract: Cardiovascular disease continues to be a major burden facing healthcare systems worldwide. In the developed world, cardiovascular magnetic resonance (CMR) is a well-established non-invasive imaging modality in the diagnosis of cardiovascular disease. However, there is significant global inequality in availability and access to CMR due to its high cost, technical demands as well as existing disparities in healthcare and technical infrastructures across high-income and low-income countries. Recent renewed interest in low-field CMR has been spurred by the clinical need to provide sustainable imaging technology capable of yielding diagnosticquality images whilst also being tailored to the local populations and healthcare ecosystems. This review aims to evaluate the technical, practical and cost considerations of low field CMR whilst also exploring the key barriers to implementing sustainable MRI in both the developing and developed world.